Propostas de educação na produção intelectual de Carvalho Neto (1926-1948) : formação e ética do advogado, educação prisional, exercício do magistério e educação para o trabalho - Lima, Maria do Socorro (2016)
This thesis aimed to investigate the education proposals in the intellectual production of the jurist, writer, journalist and Sergipe teacher, Antonio Manoel de Carvalho Neto, from books published between the years 1926 and 1948 and analyze the place of these proposals in educational projects Carvalho Neto and context of the history of Brazilian education. It was taken as the initial motivation the research developed in the Masters, in which productions were located that reflected speeches in the fields of Law and Education, through the themes raised by that intellectual. The works allowed perform analysis in the wake of the relationship between literature and history, and understand in their content and confrontation with other sources, perspectives of social representation, perception and movement of the same in the legal and educational field in Sergipe state and beyond. Three major publications were in the interests of research: Legislation and Work: controversy and doctrine (1926), which is in parliamentary speeches, Lawyers: how we learn, how we suffer, we live (1946), whose content is about the training process and social practices of lawyers and Lost Lives (1948), novel pedagogical prison. This study aimed to understand how and to what extent the intellectual production Carvalho Neto coated proposals in the field of education. Thus, it was necessary to undertake a study on the movement and ownership that such works were from the criticism they received from the press, testimonials and, above all, to investigate how the education proposals reflected in all those writings were constituted in contributions for education in Sergipe and Brazil. This research was produced from the perspective of the History of Education, from the theoretical and methodological assumptions of Cultural History. Were used as source: the written press, testimonials from Sergipe intellectuals, sources from the National Law School of the Federal University of Rio de Janeiro, Tobias Barreto Institute of Education and Culture, magazines and books. It employed some supplier categories of analysis of theoretical support for the research, such as: field, habitus, social capital, cultural capital and scientific capital of Bourdieu, ownership, distribution and representation of Chartier, social setting and civilizing process of Elias, as well as intellectuals and Sirinelli Miceli. In order to understand the object of research, the concept of legal culture Plinio Barreto helped to understand significant aspects of the legal field. The latter were considered within the limits of this research, as relevant authors for the study. Those authors led the filing of the thesis that, in the work of Carvalho Neto, there are proposals for education and training which were at the national and international agenda, from their production and. crossed decades, including: training and ethics of lawyers, education in the prison system, training of primary school teachers and their inclusion on the job and education for work. It is hoped that this research contributes to the studies in the History of Education in Sergipe, with perspective in the history of intellectuals, since, through the analysis of intellectual production Carvalho Neto, it is considered possible to record it as an intellectual participated effectively the issues related to the field of education in Brazil, with the production locus of the legal discourse, in the legal condition, writer and parliamentary.